Application of the finite element method to solve problems related to the foundations of forging machines - Đorđević, Ljubodrag; Domazet, Dragan; Trajanović, Miroslav; Popović, Predrag (Journal of Production Engineering, 1994)
During the process of shaping a product with forging hammers, the repeated impacts generate impulses that lead to vibrations and potential overloading of the components within the vibrating system. This work focuses on presenting the results of our investigation into the load distribution at the docking point, the precise positioning of the impact tool, and, most importantly, the analysis of stress levels and friction characteristics throughout the manufacturing process.